Characteristics of plates embedded with shape memory alloy wires - Tan, Wee Choon (2008)
Shape memory alloy (SMA) has the potential to be used in engineering applications. It is widely used as sensors, actuators, dampers and when embedded into composite, it demonstrates some unique mechanical and vibration properties such as the strength and damping of the composite material. In this research, the thermomechanical properties of SMA wire, the mechanical properties and vibration characteristics of composites embedded SMA wire were determined. There are two groups of SMA arrangement in the composite to be fabricated; they are without SMA wire and with unidirectional fine SMA wires (Flexinol® wire) oriented at 0°, 15°, 30° and 45° with the volume fraction of 0.08. The characteristics of SMA wire were determined using the Universal Testing Machine. The Young's modulus, stress - strain curve analysis, fundamental frequency at first mode and damping behavior of the SMA embedded composite were also done. Simulation was carried out using MA TLAB based on Brinson model and Reddy approach. The results showed that Flexinol® wire has the phase transformation temperatures at 32.840 C, 44.78°C, 52.540 C and 60.900 C and it agree well with the manufacturer technical data. The Flexinol® wire has Young's modulus during martensite and austenite of33.16 GPa and 69.59 GPa and the coefficient of stress influence during martensite and austenite of 10.76 MPa/°C and 9.08 MP~C. The Young's modulus of the composite is linearly proportional to temperature increment. The maximum fundamental frequency shifted occur at 45° for the boundary condition of C-F -F -F and C-F -C-F while for the boundary condition of C-C-C-C were at 15°, 75°, 105° and 165° if compared with the fundamental frequency at 0°. The overall highest damping occurred when 0.50 A with DC applied at the boundary condition ofCF-F-F.